Radiological findings in 210 paediatric patients with viral pneumonia: a retrospective case study - Guo, W (The British Institute of Radiology., 2012)
OBJECTIVE: The objective of this study was to assess the radiological presentations of different types of viral pneumonia in children. METHODS: Nasopharyngeal swab specimens and bronchial aspirate samples from children with acute respiratory infections were obtained and tested for influenza B, adenovirus, respiratory syncytial virus and parainfluenza (Types 1, 2 and 3) by direct immunofluorescence assay, or for influenza A (Subtype H1N1) by quantitative real-time polymerase chain reaction. The chest radiographs of the 210 confirmed cases of viral pneumonia were analysed retrospectively by two independent radiologists for the identification, characterisation and description of the distribution of imaging abnormalities. The cases were divided into six groups on the basis of confirmed causative viral agent, and radiographic findings were compared, analysed and presented. RESULTS: The abnormal chest radiograph findings consisted of bilateral patchy areas of consolidation (n=133), interstitial lung disease (n=33), diffuse areas of air space consolidation (n=29) and lobar consolidation (n=15). The abnormalities were distributed bilaterally in 195 cases and observed more frequently in the lower zones than in other regions. The radiological findings varied significantly among the six groups (p=0.0050). Pairwise comparison showed significant difference between influenza A (H1N1) and adenovirus (p=0.0031) only. CONCLUSION: The predominant radiological finding in paediatric viral pneumonia was bilateral patchy areas of consolidation. The radiological findings differed significantly only between adenovirus and influenza A pneumonia. The diagnosis of the specific causative organism requires laboratory confirmation.